2013
DOI: 10.1093/geront/gnt156
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Secondary Caregivers’ Supportive Behavior and Psychological Distress of Primary Spousal Caregivers of Cognitively Intact and Impaired Elders

Abstract: This is the first study that examined the association between availability and types of supportive behavior provided by secondary caregivers and the psychological distress of primary spousal caregivers of cognitively intact and impaired elders. The findings suggest a need to provide services that enhance the provision of emotional support from both secondary and primary caregivers to cognitively intact elders and support primary spousal caregivers to seek appropriate help according to the mood of care recipien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 44 publications
1
14
0
1
Order By: Relevance
“…younger siblings, the financial resources to pay for a domestic helper) (Penrod et al, 1995), and the failure to fulfil caring responsibilities may lead the adult-child caregivers to experience unfavourable appraisals involving shame and guilt (Hsiao et al, 2006, Ward-Griffin et al, 2007. Overall, our study found evidence of the negative impact of spousal secondary caregivers on the caregiver burden of adult-child primary caregivers of patients with dementia, which enriches our understanding of stress and support relationships in the context of family-based dementia care (Lou et al, 2013).…”
Section: Discussionmentioning
confidence: 55%
“…younger siblings, the financial resources to pay for a domestic helper) (Penrod et al, 1995), and the failure to fulfil caring responsibilities may lead the adult-child caregivers to experience unfavourable appraisals involving shame and guilt (Hsiao et al, 2006, Ward-Griffin et al, 2007. Overall, our study found evidence of the negative impact of spousal secondary caregivers on the caregiver burden of adult-child primary caregivers of patients with dementia, which enriches our understanding of stress and support relationships in the context of family-based dementia care (Lou et al, 2013).…”
Section: Discussionmentioning
confidence: 55%
“…In contrast, studies into the use of informal social support within the context of caregivers' own social network are underdeveloped. This is an important research venue because informal caregivers must provide longer care in the community (Fortinsky and Downs, 2014) and increasingly rely on the assistance and support from their social network (Lou et al, 2013).…”
Section: And Maymentioning
confidence: 99%
“…Living well in spite of dementia is not only important for the person with dementia (PwD), but also for their caregivers who face physical, emotional, and economical challenges during different phases of the disease (Schulz and Martire, 2004). Maintaining social engagement next to the caregiver role enhances feelings of wellbeing (Au et al, 2009;Lou et al, 2013)…”
Section: Introductionmentioning
confidence: 99%
“…When more than one caregiver is engaged in caregiving, the type of care provided by different caregivers affects interactions between care needs and caregiver well-being. For example, a study conducted in Hong Kong found that instrumental and emotional support provided by a secondary caregiver to a care recipient with negative mood symptoms had a negative association with the primary caregiver's well-being (Lou, Kwan, Chong, & Chi, 2015). Hence, the impact of the type of care on caregiver well-being deserves further study.…”
Section: Factors Associated With Distress Of Offspring Caregiversmentioning
confidence: 99%